Growth Behavior Evolution of Al2O3 Deposited on HOPG by Atomic Layer Deposition. Issue 1 (January 2018) - Xianglong, Nie; Dayan, Ma; Fei, Ma; Kewei, Xu
Abstract: Al2 O3 dielectrics were fabricated on highly ordered pyrolytic graphite (HOPG) by atomic layer deposition (ALD) and the effects of growth temperatures and number of ALD cycles on growth behaviors were studied. It is found that Al2 O3 preferentially grows along the step edges which promote the formation of Al2 O3 nanowires at the initial stage. Al2 O3 nanowires can exist after 100 ALD cycles at 50, 150, and 200 °C, but discontinuous Al2 O3 thin films rather than nanowires are evidenced at 100 °C. Moreover, the Al2 O3 layers evolve into continuous thin films with increasing number of ALD cycles. It suggests the growth behavior undergoes a transition from three-dimensional mode to quasi two-dimensional mode with increasing number of ALD cycles. The rates of transition and lateral growth are dependent on growth temperatures. Raman spectra indicate that HOPG maintains undamaged and greatly reserves its original properties after the deposition of Al2 O3 . The results are of great significance to the fabrication of high-quality dielectric layers on graphene as well as the related devices.